Nutrient utilization and energy balance profile in probiotic supplemented asian elephants - Dharmendra Chharang; Sheela Choudhary (Eurasian Journal of Veterinary Sciences)
Aim: A study was methodized to evaluate whether supplementation of probiotics could impact the utilization of nutrients and energy in Asian elephants. Materials and Methods: Eighteen elephants were randomly selected for 60 days experiment including five days of the digestibility trial and divided into three groups with six elephants each i.e. control with no probiotic (T1) and the other two with probiotics Lactobacillus acidophilus in T2 and Saccharomyces cerevisiae in T3 groups at 1 × 109 CFU/gm concentrate per 50 kg body weight/ day orally. Results: The intakes of ether extract and total ash revealed significant whereas the digestibility coefficients of total ash and acid-insoluble ash exhibited a highly significant effect of treatment. However, other values of intakes and the digestibility coefficients of proximate principles and fibre fractions could not reveal any significant effect. Practical nutritional worth, plane of nutrition and energy balance profile were also found to be nonsignificant among the groups. Increasing trend of intake and the digestibility of energy; and the relative difference was associated with increased DM intake and NDF digestibility. The mean values for TDN%, NR, digestible DM and OM intakes and TDN intake were obtained to be higher for probiotic supplemented groups than the control group. Conclusion: It is concluded that probiotic supplementation could not exhibit any significant effect on nutrients and energy utilization in elephants. However, further research is needed to examine the effects of high doses, strain and viability of the probiotics.